The 4E knowledge management model for Philippine higher education institutions - Bitera, Ma. Xenia Z. (University of the Philippines-Diliman, 2019)
This study was aimed at developing knowledge management (KM) model for adoption of higher educational institutions in the Philippines. Five universities across the country were purposively selected to shed light on their knowledge management adoption and practices as basis for the KM model for Philippine context. This inquiry utilized the qualitative, multi-case study research design. The findings revealed that the knowledge management operation, understanding, and identification of organizational knowledge were inadequate. Although the process to acquire, create, store, share, use and assess were practiced among universities, some were not yet fully delineated and performed. The outcomes of knowledge management implementation greatly support the achievement of higher education mission, improvement of organizational management, and development and utilization of knowledge capital. The educational administrators applied the basic management functions of planning, organizing, leading and controlling in spearheading the knowledge management of the university. The strategy, structure, and support, and implementation fortify the adoption of knowledge management. This study concludes that Knowledge Management in the Philippine higher education institutions is still in the infancy stage based on the presenting findings of this study on the lack of doable KM framework/model, experts, and formal training. Four major themes emerged that were translated into rudiments of the Knowledge Management model namely: Empowering, Enabling. Enacting, and Engaging. Hence, the 4E Knowledge Management model is advanced. It starts with the empowering rudiments as the initial process that leads to the enabling rudiments to operationalized intended results with the support of enacting rudiment with the application of engaging rudiments.